A case of cavernous hemangioma of the temporalis muscle. Issue 6 (November 2020) - Watanabe, Hideki; Osano, Hitoshi; Naitou, Hiromi; Mori, Yoshiyuki
Abstract: Hemangiomas most commonly occur in the skin or mucosa and are rare in skeletal muscle. There have been almost no reports of their development in skeletal muscle of the head and neck region. A case of cavernous hemangioma of the temporalis muscle is reported along with a short discussion of the literature. A 69-year-old woman presented to our department with a chief complaint of swelling in the left temporal region. She had noticed a painless mass in this region around six months earlier and had consulted a local dental clinic, which had referred her to our department for further investigation and treatment. On general physical examination, she was of moderate build and well nourished. External oral examination showed a palpable, elastic-soft, semispherical mass in the left temporal region measuring 37 mm × 36 mm. Internal oral examination showed nothing of note. A clearly demarcated hyperintensity between the left temporalis muscle and the left temporalis fascia was visible on T2-weighted and short tau inversion recovery (STIR) magnetic resonance imaging (MRI), and this was clinically diagnosed as a tumor of the left temporal region. Thus, tumor enucleation of the left temporal region was scheduled and performed under general anesthesia. The histopathological diagnosis was cavernous hemangioma. The patient's postoperative course has been good, with no recurrence nine months after surgery.